As dinâmicas Intraorganizacionais em um serviço de saúde e educação: análise de redes sociais - Fazion, Cintia Bincoleto (2017)
This thesis proposes to analyze the interorganizational dynamics of cooperation and knowledge exchange between professionals who are part of a multidisciplinary team from a health and education service, from a private, non-profit organization. An investigation was carried out to find out whether there is a process of network integration and exchanges of knowledge and collaboration between them. The quantitative and qualitative research was carried out by applying a questionnaire to identify the existence of a network in the institution. The profile of the professionals, their competences, their positioning and the type of knowledge they shared were characterized. The data was entered in Excel and processed in the network analysis software, ORA.NetScenes. The network analysis identified four groups associated with the sectors in which the agents operate and presented a relatively centralized structure and with a few specialists with a chance of sharing knowledge and dynamics. The most indicated and the possible relational exchanges existing in the groups were verified . The institution presented a low density of links between the professionals and a restricted reciprocity in the relations between the agents. In order to stimulate individuals to act in a network, it is important to foster actions that stimulate interdisciplinary exchanges among professionals, resulting in benefits for the organization and the public served. In spite of developing a network analysis, not all the possibilities among the agents of the organization were explored